Glycine as a lixiviant for the leaching of low grade copper-gold ores - Tanda, Bennson Chemuta (Curtin University, 2017)
The continuous depletion of high grade gold ores has shifted research focus towards the processing of low grade, complex ores containing impurities such as copper which is detrimental to the traditional cyanidation process. Alkaline glycine solution selectively leached copper and gold over impurity elements such as Fe, Ca, Mg and Si from copper – gold ores. Copper was recovered from solution by solvent extraction and gold could be recovered by carbon adsorption while glycine is recycled.